2009
DOI: 10.1016/s0079-6123(09)17526-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of control of posture and locomotion after a spinal cord injury: solutions staring us in the face

Abstract: Over the past 20 years, tremendous advances have been made in the field of spinal cord injury research. Yet, consumed with individual pieces of the puzzle, we have failed as a community to grasp the magnitude of the sum of our findings. Our current knowledge should allow us to improve the lives of patients suffering from spinal cord injury. Advances in multiple areas have provided tools for pursuing effective combination of strategies for recovering stepping and standing after a severe spinal cord injury. Musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 131 publications
(166 reference statements)
0
50
0
Order By: Relevance
“…Spinal locomotor networks in humans and other vertebrates are capable of generating rhythmic muscle activity (Dietz, 2003;Dimitrijevic et al, 1998;Grillner, 1985;Rossignol, 2000;Rossignol et al, 2006;Shik and Orlovsky, 1976). However, activating this network in humans without functional descending motor pathways has proven to be difficult (Dietz et al, 1995;Ferris et al, 2004;Fong et al, 2009;Wirz et al, 2001). Some supraspinal locomotor centers are organized hierarchically in the brainstem, cerebellum, and cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal locomotor networks in humans and other vertebrates are capable of generating rhythmic muscle activity (Dietz, 2003;Dimitrijevic et al, 1998;Grillner, 1985;Rossignol, 2000;Rossignol et al, 2006;Shik and Orlovsky, 1976). However, activating this network in humans without functional descending motor pathways has proven to be difficult (Dietz et al, 1995;Ferris et al, 2004;Fong et al, 2009;Wirz et al, 2001). Some supraspinal locomotor centers are organized hierarchically in the brainstem, cerebellum, and cortex.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] From the results of recent studies in mice and rats with motor complete paralysis we know that the lumbosacral spinal cord can be neuromodulated electrically and pharmacologically to enable motor control, including full weight-bearing stepping. 1,3,4 Recently we reported that four human patients having been motor complete for 2 or more years regained the ability to stand and voluntarily generate leg movements in the supine position with the aid of epidural stimulation. 5,6 Although the subjects were able to generate flexor movements with considerable precision, minimal locomotor-like movements were generated.…”
mentioning
confidence: 99%
“…It is known that regular application of some factors, including training, electrical and pharmacological stimulation of the spinal cord, or their combination, results in restoration of locomotor functions in spinal animals (Antri et al 2003(Antri et al , 2005Courtine et al 2009;Edgerton et al 2008;Fong et al 2005Fong et al , 2009Gerasimenko et al 2008;Rossignol et al 2001). These findings suggest that such treatments prevent spontaneous changes in the isolated spinal network, leading to disintegration of locomotor central pattern generator, and induce plastic changes, resulting in the restoration of locomotor function.…”
mentioning
confidence: 99%